2009
DOI: 10.1007/s00268-009-0374-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypo‐ and Hypernatraemia in Surgical Patients: Is There Room for Improvement?

Abstract: Four percent of surgical inpatients developed dysnatraemias, which were associated with increased mortality. Fluid balance documentation was suboptimal and daily weights were not measured routinely, even in patients with severe electrolyte derangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
0
18
0
2
Order By: Relevance
“…In a study conducted by Herrod et al, on 1383 surgical patients, it was shown that the patients with dysnatraemias had a considerably higher mortality than the patients with normal serum sodium levels. 11 In another study conducted on orthopaedic patients, it was observed that hyponatraemia was related with a 2.1-fold rise in mortality in mild cases and 4.6-fold rise in severe cases. 12 The major proportion of dysnatraemia in elderly persons can be due to the presence of concurrent disease such as hyperglycemia and the syndrome of inappropriate ADH secretion (SIADH).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Herrod et al, on 1383 surgical patients, it was shown that the patients with dysnatraemias had a considerably higher mortality than the patients with normal serum sodium levels. 11 In another study conducted on orthopaedic patients, it was observed that hyponatraemia was related with a 2.1-fold rise in mortality in mild cases and 4.6-fold rise in severe cases. 12 The major proportion of dysnatraemia in elderly persons can be due to the presence of concurrent disease such as hyperglycemia and the syndrome of inappropriate ADH secretion (SIADH).…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] This cause of CDI is usually transient, but it can result in significant hypernatremia in postoperative patients. 39 These patients have increased serum sodium concentrations and osmolality, and usually have hyposthenuric urine (unless severely dehydrated, in which case they may approach isosthenuria). Clinical experience indicates that this is most common in postoperative gastric dilatation-volvulus cases, but other surgical cases, including gastrointestinal resection and anastomosis, septic peritonitis, hemoabdomen, and occasionally thoracotomy, may also be affected.…”
Section: Postoperative Derangements Hypernatremiamentioning
confidence: 99%
“…166 It has been shown reproducibly that particularly hypernatremia is a risk factor for increased mortality. [167][168][169] Hyponatremia, which is more common, is noted to be a risk factor for bone fracture. [170][171][172] Hyperkalemia is a concern as tubular dysfunction impairs the secretion of potassium.…”
Section: Renalmentioning
confidence: 99%